Laypersons' Esthetic Perception of Different Dentogingival Characteristics Based on Smile Dynamics: Cross-Sectional Study - Adriana S. Malheiros; Julianne R. Barboza; Sebastião M. Pinheiro Neto; Daniela B. Dibai; Etevaldo M. Maia Filho; Célia Maio Pinzan-Vercelino; Meire C. Ferreira; Rudys R. J. Tavarez (Hindawi Limited, 2024)
This study aimed to evaluate laypersons' esthetic perception of different dentogingival characteristics based on smile dynamics. Six voluntary models were selected, with only one presenting dentogingival characteristics within esthetic standards: white teeth, good alignment, and adequate gingival contour. Two videos were then produced. One video focused on the mouth, whereas the other focused on the entire face of the model, to ensure that the dynamics of the smile could be evaluated. For the evaluation, 200 laypeople were asked to rank the models from first to sixth place in their order of preference. Laypeople were required to justify their reasons for choosing the first and last places. The obtained data were subjected to descriptive and inferential statistical analyses. The results showed that smile and face dynamics influenced the perception of dentogingival characteristics and facial esthetics. No significant changes were observed. However, a gummy smile accompanied by dental alterations was observed in the video of the mouth and was masked by the facial set exposed in the video of the face. A diastema between the central incisors was decisive for negative evaluation of both the mouth and face. The standard model was rated as the most pleasing. Smiles and facial dynamics influence the perception of dentogingival characteristics. Smile and facial dynamics influence the perception of dentogingival alterations among Brazilian laypeople. Diastema is an alteration that interferes with the isolated evaluation of the lower third of the face and the facial set.